Flame AAS determination of metal ions in fuel ethanol after preconcentration on acid carboxymethylcellulose (CMCH) - Padilha, P. M.; Padilha, CCF; Rocha, Julio Cesar [UNESP] (Elsevier B.V., 1999)
This paper describes the preparation of acid carboxymethylcellulose (CMCH), and the results of a study on the adsorption and preconcentration (using batch and flow-through column methods) of Cd(II), Cu(II), Cr(III), Fe(III), Ni(II) and Zn(II) in ethanol medium. The adsorption capacities for each metallic ion were (in mmol g(-1)) Cd(II) = 0.92; Cu(II) = 1.45; Cr(III) = 1.70; Fe(III) = 1.60; Ni(II) = 1.30; and Zn(II) = 1.10. By means of the flow-through method, a recovery of ca. 100% of the metallic ions adsorbed in a column packed with 2 g of CMCH was found when 5.0 mL of 1.0 mol L-1 hydrochloric acid were used as eluent. An enrichment factor of 20 (100 mt solution containing 50 mu g L-1 of the metallic ions, concentrated to 5.0 mt) was obtained by this preconcentration procedure. The sorption-desorption procedure applied allowed the development of a preconcentration and Flame AAS quantification method of metallic ions in fuel ethanol at trace levels.
Keywords: preconcentration; carboxymethylcellulose; metallic ions in ethanol; flame atomic absorption spectroscopy